Effects of CO2 concentration and light intensity on the growth and biochemical composition of Chlorella vulgaris cultured in recirculating aquaculture system’s effluent - Kannangara, Ruchira (2024)
Microalgae cultivation has gained more attention recently due to the produced high-value biomass, which has many useful applications. The effluents from recirculating aquaculture systems (RAS) typically contain a high nutrient content, and the RAS system produces excess CO2, which together could be utilized to cultivate microalgae while increasing the sustainability of the system. This study tested how light intensity and CO2 concentration affects the growth and biochemical composition of the microalgae Chlorella vulgaris grown in RAS effluent. C. vulgaris was cultivated at two light intensities (50 and 90 μmol photons m−2 s−1) and at two CO2 concentrations (room air with 0.04% of CO2 and air stripped from RAS trickling filter with about 0.1% of CO2) for 10 days in photobioreactors using RAS effluent. The results indicated that biomass (dry weight and ash free dry weight) was significantly enhanced with increased light intensity and CO2 concentration. Although the growth rate was not affected by either of these factors, the achieved growth rates were comparable to that of some previous studies on C. vulgaris. There was a positive effect also on the lipid content of C. vulgaris by increased light intensity and increased CO2 concentration. Furthermore, phosphate uptake by C. vulgaris from RAS effluent was almost 100% for all the cultures, and increasing the CO2 concentration and light intensity led to the uptake of almost all the nitrate from C. vulgaris cultures. This study suggests that cultivating C. vulgaris to produce valuable microalgal biomass in RAS effluent can be enhanced by treating the cultures with high light intensity and increased CO2 concentration, while also improving the RAS system's sustainability by reducing nitrate and CO2 emissions.